Posted by **ROBIN** on Monday, July 15, 2013 at 10:34pm.

Explain the difference between cos^-1x and (cos x)^-1

## Answer This Question

## Related Questions

- math - Determine exact value of cos(cos^-1(19 pi)). is this the cos (a+b)= cos a...
- Math - Explain how to do this with steps please. 1. Simplify cos(x-y)+cos(x+y)/...
- calculus - Differentiate. y= (cos x)^x u= cos x du= -sin x dx ln y = ln(cos x)^x...
- Calc. - Differentiate. y= (cos x)^x u= cos x du= -sin x dx ln y = ln(cos x)^x ln...
- Math - Explain how to do this with steps please. 1. Simplify cos(x-y)+cos(x+y)/...
- Math - Solving Trig Equations - What am I doing wrong? Equation: sin2x = 2cos2x ...
- pre-cal - Simplify the given expression........? (2sin2x)(cos6x) sin 2x and cos ...
- maths - Find the roots of z^6 + 1 and hence resolve z^6 + 1into read quadratic ...
- maths - Find the roots of z^6 + 1 and hence resolve z^6 + 1into read quadratic ...
- math - how would you prove that sin^2(a)-cos^2(b)= sin^2(b)-cos^2(a). i'm not ...

More Related Questions